Classical and Non-classical Fibrosis Phenotypes Are Revealed by Lung and Cardiac Like Microvascular Tissues On-Chip - Akinbote, Akinola; Beltran-Sastre, Violeta; Cherubini, Marta; Visone, Roberta; Hajal, Cynthia; Cobanoglu, Defne; Haase, Kristina (Frontiers in Physiology, 2021)
Fibrosis, a hallmark of many cardiac and pulmonary diseases, is characterized by excess deposition of extracellular matrix proteins and increased tissue stiffness. This serious pathologic condition is thought to stem majorly from local stromal cell activation. Most studies have focused on the role of fibroblasts; however, the endothelium has been implicated in fibrosis through direct and indirect contributions. Here, we present a 3D vascular model to investigate vessel-stroma crosstalk in normal conditions and following induced fibrosis. Human-induced pluripotent stem cell-derived endothelial cells (hiPSC-ECs) are co-cultured with (and without) primary human cardiac and lung fibroblasts in a microfluidic device to generate perfusable cardiac- and pulmonary-like microvasculature. Endothelial barrier function, vascular morphology, and matrix properties (stiffness and diffusivity) are differentially impacted by the presence of stromal cells. These vessels (with and without stromal cells) express inflammatory cytokines, which could induce a wound-healing state. Further treatment with transforming growth factor-β (TGF-β) induced varied fibrotic phenotypes on-chip, with lung fibroblasts resulting in increased stiffness and smooth muscle actin expression. Taken together, our work demonstrates the strong impact of stromal-endothelial interactions on vessel formation and extravascular matrix regulation. The role of TGF-β is shown to affect co-culture microvessels differentially and has a severe negative impact on the endothelium without stromal cell support. Our human 3D in vitro model has the potential to examine anti-fibrotic therapies on patient-specific iPSCs in the future.